Characterization of "sandwich" wulfenite from the Ojuela Mine, Mapimi, Mapimi Municipality Durango, Mexico evidence of preferred secondary nucleation on selected wulfenite faces - Kloprogge, J. Theo; Valera-Gadot, Jessebel P. (Vol. 150, No.2 (April 2021), pages 513-519.)
''This paper describes the formation of "sandwich" wulfenite. Banded wulfenite from the Ojuela Mine, Mapimi, Durango, Mexico, have been found since 2017, but and explanation for the band formation has not been provided. x-ray diffraction (XRD) showed the wulfenite to have a tetragonal unit cell of a=5.4374(1), c=12.1123(7) A"-title page.